Effects of seasonal variations and collection methods on the mineral composition of propolis from Apis mellifera Linnaeus Beehives - Souza,E. A. (2016)
Abstract The effects of seasonal variations and the methods of collection of propolis produced by Africanized honey bees Apis mellifera Linnaeus, 1758, on the composition of constituent minerals such as magnesium (Mg), zinc (Zn), iron (Fe), sodium (Na), calcium (Ca), copper (Cu), and potassium (K) were evaluated. Propolis was harvested from 25 beehives by scraping or by means of propolis collectors (screen, “intelligent” collector propolis [ICP], lateral opening of the super [LOS], and underlay method). During the one-year study, the propolis produced was harvested each month, ground, homogenized, and stored in a freezer at -10 ºC. Seasonal analyses of the mineral composition were carried out by atomic absorption spectrophotometry and the results were evaluated by analysis of variance (ANOVA), followed by Tukey-Kramer’s test to compare the mean values (p<0.05). The results showed that seasonal variations influence the contents of 5 minerals (Mg, Fe, Na, Ca, and Cu), and the propolis harvesting method affects the contents of 4 minerals (Mg, Zn, Fe, and Ca).